2014
DOI: 10.1007/s12032-014-0365-1
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin phosphate-induced autophagy effectively enhances cell apoptosis of human breast cancer cells

Abstract: Oridonin is an active diterpenoid, which was extracted from traditional Chinese herbs and had been widely used in clinical treatment nowadays. Oridonin phosphate is one of the derivatives of oridonin. In the present study, we explored its anti-tumor effect and investigated the molecular mechanism of oridonin phosphate in breast cancer cell lines. Firstly, cell viability was analyzed by MTT assay. The breast cancer cells were treated with increasing concentrations of oridonin phosphate for 24, 48 and 72 h, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…In addition, p53 has been shown to play a critical role in autophagy modulation (38). Upon activation, autophagy may promote or inhibit apoptosis depending on the level of the insult, and the interplay between these two cellular processes has been the subject of intensive relationship (17,39). Associated with colistin therapy, nephrotoxicity and neurotoxicity remain poorly characterized adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, p53 has been shown to play a critical role in autophagy modulation (38). Upon activation, autophagy may promote or inhibit apoptosis depending on the level of the insult, and the interplay between these two cellular processes has been the subject of intensive relationship (17,39). Associated with colistin therapy, nephrotoxicity and neurotoxicity remain poorly characterized adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy participates in organelle turnover and in the bioenergetic management of starvation stresses, pathogen infection, and hypoxia in order to maintain cellular homeostasis (14,15). A number of stimuli can induce autophagy, apoptosis, or both, and recent studies suggest that autophagy delays or promotes apoptosis under certain conditions (16,17). For example, treatment of cells with pemetrexed and simvastatin promoted autophagy and inhibited apoptosis (16), while oridonin phosphate induced autophagy and enhanced apoptotic cell death (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both autophagy and apoptosis are forms of programmed cell death and play important roles in homeostasis and diseases (17). Recent studies have suggested that autophagy may defer or promote the activation of apoptosis under certain circumstances (e.g., SIRT1 protects against apoptosis by promoting autophagy and oridonin phosphate-induced autophagy effectively enhances cell apoptosis) (18,19). Autophagy and apoptosis have a very complex relationship, and the precise mechanism remains to be determined.…”
mentioning
confidence: 99%
“…1A), a bitter tetracyclin diterpenoid compound, may be isolated from Rabdosia rubescens, Isodon japonicus Hara and Isodon trichocarpus, which are widely distributed in China, Japan and Korea (7). Studies show that Ori exhibits potent anticancer activity against a wide range of cancer cell types, including those from prostate, breast, pancreatic and non-small cell lung cancer, leukemia, glioblastoma multiforme and human melanoma cells (8)(9)(10)(11)(12)(13). However, to the best of our knowledge, no study has shown the effect and the potential mechanism of Ori reversing MDR of human gastric cancer.…”
Section: Introductionmentioning
confidence: 99%